Pilot plant for the reprocessing of irradiated nuclear fuels - Kaufmann, Ferdy (Comisión Nacional de Energía Atómica; Argentina, 1967)
Fil: Kaufmann, Ferdy Comisión Nacional de Energía Atómica; Argentina